Distinct localizations and roles of non‐muscle myosin II during proplatelet formation and platelet release. (1st April 2015) - Badirou, I.; Pan, J.; Souquere, S.; Legrand, C.; Pierron, G.; Wang, A.; Eckly, A.; Roy, A.; Gachet, C.; Vainchenker, W.; Chang, Y.; Léon, C.
Summary Background At the end of maturation, megakaryocytes (MKs) form long cytoplasmic extensions called proplatelets (PPT). Enormous changes in cytoskeletal structures cause PPT to extend further, to re‐localize organelles such as mitochondria and to fragment, leading to platelet release. Two non‐muscle myosin IIs (NMIIs) are expressed in MKs; however, only NMII‐A (MYH9), but not NMII‐B (MYH10), is expressed in mature MKs and is implicated in PPT formation. Objectives To provide in vivo evidence on the specific role of NMII‐A and IIB in MK PPT formation. Methods We studied two transgenic mouse models in which non‐muscle myosin heavy chain (NMHC) II‐A was genetically replaced either by II‐B or by a chimeric NMHCII that combined the head domain of II‐A with the rod and tail domains of II‐B. Results and Conclusions This work demonstrates that the kinetic properties of NM‐IIA, depending on the N‐terminal domain, render NMII‐A the better NMII candidate to control PPT formation. Furthermore, the carboxyl‐terminal domain determines myosin II localization in the constriction region of PPT and is responsible for the specific role of NMII in platelet release.